2016
DOI: 10.1073/pnas.1518952113
|View full text |Cite|
|
Sign up to set email alerts
|

Diverse high-torque bacterial flagellar motors assemble wider stator rings using a conserved protein scaffold

Abstract: Although it is known that diverse bacterial flagellar motors produce different torques, the mechanism underlying torque variation is unknown. To understand this difference better, we combined genetic analyses with electron cryo-tomography subtomogram averaging to determine in situ structures of flagellar motors that produce different torques, from Campylobacter and Vibrio species. For the first time, to our knowledge, our results unambiguously locate the torque-generating stator complexes and show that diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
262
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(291 citation statements)
references
References 71 publications
14
262
2
Order By: Relevance
“…Spirochete species, such as T. primitia and B. burgdorferi, have 16 putative stator units as visualized by cryo-ET (29,30). Recent data have suggested that the C. jejuni motor can possess 17 stator units while Vibrio fischeri has 13 stator units (57). Our data indicate that the H. pylori motor can assemble 18 stator units, potentially allowing for the generation of higher torque than other bacterial species.…”
Section: Discussionmentioning
confidence: 66%
“…Spirochete species, such as T. primitia and B. burgdorferi, have 16 putative stator units as visualized by cryo-ET (29,30). Recent data have suggested that the C. jejuni motor can possess 17 stator units while Vibrio fischeri has 13 stator units (57). Our data indicate that the H. pylori motor can assemble 18 stator units, potentially allowing for the generation of higher torque than other bacterial species.…”
Section: Discussionmentioning
confidence: 66%
“…3). Altogether, these studies can be used to gain further insight into the evolution of the multiprotein complex of the flagellar motor (57).…”
Section: Expanding the Toolboxmentioning
confidence: 99%
“…Disk complex components of the C. jejunimotor have been identified using transposon screens [51,55,56]. candidates for further components of the C. jejunimotor [55].…”
Section: Motor 133mentioning
confidence: 99%
“…C. jejuni and H. hepaticus exhibit wider C-rings 123 with diameter 53 nm [40], while the W. succinogenesC-ring appears approximately ~60 nm wide in thin-124 section EM [48]. Inspection of this wider C-ring reveals an inner lobe that is elongated relative to that in 125 Salmonella, suggestive of an additional domain or protein responsible for "spacing" the C-ring wider [51]. 126…”
mentioning
confidence: 97%
See 1 more Smart Citation